1993
DOI: 10.1203/00006450-199309000-00022
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nω-Nitro-L-Arginine Methylester on Hypoxic Vasoconstriction in the Neonatal Pig Lung

Abstract: ABSTRACT. This study was carried out to determine the influence and site of action of Nu-nitro-L-arginine methylester, an L-arginine analogue, on basal pulmonary vascular tone and hypoxic vasoconstriction in neonatal pig lungs. We studied isolated lungs from pigs, age 14.5 2 0.5 (SD) d and weight 3.6 +: 0.7 kg, perfused with autologous blood a t a constant flow rate. The arterial-venous occlusion method was used to determine sites of action upstream and downstream of the double occlusion pressure (Pd) during b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…For example, Fike reported in neonatal pigs (20)(21)(22)(23). As a positive control in two and Kaplowitz (28) found that injection of papaverine resulted animals at the end of the experiment, 0.3 mg/kg neostigmine in a decrease in PVR in neonatal pig lungs, and we found that was given i.v., which resulted in a doubling of pulmonary resist-infusion of acetylcholine decreased PVR in a similar preparation ance from 4.0 * 1.1 cm H20/mL/s baseline to 7.8 k 2.8 cm (19). These differences between pigs and lambs may suggest H20/mL/s after neostigmine administration.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, Fike reported in neonatal pigs (20)(21)(22)(23). As a positive control in two and Kaplowitz (28) found that injection of papaverine resulted animals at the end of the experiment, 0.3 mg/kg neostigmine in a decrease in PVR in neonatal pig lungs, and we found that was given i.v., which resulted in a doubling of pulmonary resist-infusion of acetylcholine decreased PVR in a similar preparation ance from 4.0 * 1.1 cm H20/mL/s baseline to 7.8 k 2.8 cm (19). These differences between pigs and lambs may suggest H20/mL/s after neostigmine administration.…”
Section: Resultsmentioning
confidence: 88%
“…After 15 min the measurements described above were repeated. We have previously found that the neonatal pig has a stable hypoxic response over this time period (19). Finally, the pig breathed room air, and after 2 or 3 min, when the pulmonary artery pressure had stabilized at the baseline value, the pig was exsanguinated and the lungs removed for the determination of wet-to-dry weight ratios.…”
mentioning
confidence: 99%
“…On the one hand, HPV was enhanced in intact and isolated lungs treated with NOS antagonists (60,78,114,185,214,264,379,449,477,509,512,640,752,1058,1107,1368,1699,1825,1968,2138) and isolated nonprecontracted pulmonary arteries treated with NOS antagonists, Hb (which binds NO), or inhibitors of soluble guanylyl cyclase (393, 1104,1411,1418). Moreover, HPV was exaggerated in transgenic mice with complete or partial eNOS deficiency (495, 1106), but blunted in rat and mouse lungs overexpressing eNOS and/or iNOS (277, 887,896).…”
Section: Interaction With Smooth Musclementioning
confidence: 99%
“…Numerous studies have utilized NOS antagonists to investigate the role of NO in maintaining low normal pulmonary vascular tone. In the neonate, studies clearly demonstrate a critical role for NO as a modulator of PVR (143,228,455). In the adult lung, however, contradictory results have been reported.…”
Section: Nitric Oxidementioning
confidence: 99%